Dinners with Ruth : a memoir on the power of friendships - Totenberg, Nina; OverDrive, Inc. (Waterville : Thorndike Press, 2022)
"Four years before Nina Totenberg was hired at NPR, where she cemented her legacy as a prizewinning reporter, and nearly twenty-two years before Ruth Bader Ginsburg was appointed to the Supreme Court, Nina called Ruth. A reporter for The National Observer, Nina was curious about Ruth's legal brief, asking the Supreme Court to do something revolutionary: declare a law that discriminated "on the basis of sex" to be unconstitutional. In a time when women were fired for becoming pregnant, often could not apply for credit cards or get a mortgage in their own names, Ruth patiently explained her argument. That call launched a remarkable, nearly fifty-year friendship. Dinners with Ruth is an extraordinary account of two women who paved the way for future generations by tearing down professional and legal barriers. It is also an intimate memoir of the power of friendships as women began to pry open career doors and transform the workplace. At the story's heart is one, special relationship: Ruth and Nina saw each other not only through personal joys, but also illness, loss, and widowhood. During the devastating illness and eventual death of Nina's first husband, Ruth drew her out of grief; twelve years later, Nina would reciprocate when Ruth's beloved husband died. They shared not only a love of opera, but also of shopping, as they instinctively understood that clothes were armor for women who wanted to be taken seriously in a workplace dominated by men. During Ruth's last year, they shared so many small dinners that Saturdays were "reserved for Ruth" in Nina's house. Dinners with Ruth also weaves together compelling, personal portraits of other fascinating women and men from Nina's life, including her cherished NPR colleagues Cokie Roberts and Linda Wertheimer; her beloved husbands; her friendships with multiple Supreme Court Justices, including Lewis Powell, William Brennan, and Antonin Scalia, and Nina's own family--her father, the legendary violinist Roman
Totenberg, and her "best friends," her sisters. Inspiring and revelatory, Dinners with Ruth is a moving story of the joy and true meaning of friendship"--
Electronic audio file.
Electronic reproduction.
Keywords: Totenberg, Nina -- Friends and associates; Ginsburg, Ruth Bader, -- 1933-2020 -- Friends and associates; Advantage title -- Fiction; Radio broadcasters -- United States -- Biography; Judges -- United States -- Biography; Female friendship; BIOGRAPHY & AUTOBIOGRAPHY / Personal Memoirs; BIOGRAPHY & AUTOBIOGRAPHY / Lawyers & Judges; Electronic audio books